A Study on Attachment Orientations of Married Couples Living in the Suburbs of Kuala Lumpur and Rural Areas of Kota Bahru, Kelantan, Malaysia. (April 2017) - Abdul Kadir, Nor Ba'yah; Wan Sulaiman, Wan Shahrazad; Desa, Asmawati; Omar, Fatimah; Halim, Fatimah Wati; Yusooff, Fatimah
This study investigated the attachment orientations among married couples living in the suburbs of Kuala Lumpur and rural areas of Kota Bahru, Kelantan, Malaysia. The door-to-door approach was used to collect the data. The Experience in Close Relationship–Revised version and the Experiences in Close Relationship–Relationship Structures were used to measure attachment orientations. The results showed that husbands scored higher in anxiety and lower in avoidance than their wives. The participants from Kuala Lumpur reported more anxiety and more avoidance for the partner domain but less avoidance for the best friend domain. The implications of the study as well as the need for understanding attachment orientations for married couples are discussed.